Evaluation of Upper Secondary Schools on efficiency and productivity change in 2016-2019: Empirical evidence from schools in the region in Central Greece - Stylianos Gr. Margaritis (SPOUDAI - Journal of Economics and Business, 2021)
The study investigates the relative efficiency and productivity change of Upper Secondary Schools in the region of Central Greece during the period 2016-2019. It measures the technical and scale efficiencies and productivity change by using DEA output-oriented and Malmquist analysis. Empirical analysis reveals that few are efficient and most are inefficient . The efficiency under constant returns to scale varies in interval [0.666-1.000] and under variable returns to scale in interval [0.759-1.000], with average efficiency score being 0.875 and 0.923 respectively. This means that given the quantities of inputs, Upper Secondary Schools could produce, on average, more quantities of outputs by 12.5% or 7.7% respectively. The scale efficien cy varies in the interval [0.745 -1.000] and the mean is 0.948. The findings suggest that schools on average refrain 5 .2% from the optimal scale. The results show that average values of efficiency are moving around the average performance of Upper Secondary Schools of other countries in the world and the European Union. The total factor productivity change of production factors has risen by an annual average of 5.2% relative to the base year 2016.
Keywords: C14; J48; P41; 330; Upper Secondary Schools; Efficiency; P roductivity; Data Envelopment Analysis; Malmquist analysis